The Role of Triacylglycerol in Plant Stress Response - Junhao Lu; Yang Xu; Juli Wang; Stacy D. Singer; Guanqun Chen (Plants, 2020)
Vegetable oil is mainly composed of triacylglycerol (TAG), a storage lipid that serves as a major commodity for food and industrial purposes, as well as an alternative biofuel source. While TAG is typically not produced at significant levels in vegetative tissues, emerging evidence suggests that its accumulation in such tissues may provide one mechanism by which plants cope with abiotic stress. Different types of abiotic stress induce lipid remodeling through the action of specific lipases, which results in various alterations in membrane lipid composition. This response induces the formation of toxic lipid intermediates that cause membrane damage or cell death. However, increased levels of TAG under stress conditions are believed to function, at least in part, as a means of sequestering these toxic lipid intermediates. Moreover, the lipid droplets (LDs) in which TAG is enclosed also function as a subcellular factory to provide binding sites and substrates for the biosynthesis of bioactive compounds that protect against insects and fungi. Though our knowledge concerning the role of TAG in stress tolerance is expanding, many gaps in our understanding of the mechanisms driving these processes are still evident. In this review, we highlight progress that has been made to decipher the role of TAG in plant stress response, and we discuss possible ways in which this information could be utilized to improve crops in the future.